Numerical Analysis Of Tbm Tunnel Behaviour And Support Under High Stress Rock Masses In Pahang-Selangor Raw Water Transfer Tunnel - Heyam Hussein, Shaalan (2019)
This study aims to evaluate the rock overstressing that occurred in the critical cases of the TBM tunnel of the Pahang-Selangor raw water transfer project. Based on the insitu stress conditions and rock compressive strength, a possible rock failure in the form of spalling is evaluated at the tunnel sidewalls under high stresses. A numerical analysis with different approaches is adopted to simulate the extent, shape and depth of the actual failure. These approaches include the elastic analysis model, elasticperfectly- plastic model, elastic-brittle-plastic model with (residual friction r m = 0 and residual cohesion r S = 0.11) and instantaneous Cohesion-Softening Friction- Hardening (CSFH) model. A parametric study on the CSFH model strength parameters is implemented to describe the influence of the strength parameters on the extent, shape and depth of the failure, as well as to investigate which parameters could simulate the actual failure depth properly. Results are compared with the observed failure to determine which approach can predict the actual failure. Results of the CSFH model predict the actual failure depth and shape accurately since it is an elastic-brittle plastic model and can simulate the loss in the cohesion strength to low residual strength after failure. A parametric study is performed to investigate the influence of the tunnel parameters on the simulated failure zone. These parameters are tunnel lining thickness, tunnel size, tunnel overburden depth and rock scaling. Results demonstrate that the stability of the tunnel improves by decreasing the tunnel depth and removing the loose rock mass. One of the most important support elements of tunnel constructions under high overburden depth is steel fibre reinforced shotcrete (SFRS). Generally, shotcrete material shows a time-dependent behaviour after a few hours of application. Therefore, a new constitutive model of shotcrete is utilised to evaluate the time-dependent behaviour of the SFRS lining under high stresses. The SFRS lining is analysed in term of major stresses and vertical displacement using the shotcrete model and an elastic analysis method with a constant young modulus of elasticity. Considerable differences in shotcrete lining stresses are achieved when using the elastic analysis compared with that obtained by the shotcrete model. Furthermore, an attempt is made to investigate the influence of the shotcrete model input parameters on the time-dependent behaviour of the shotcrete lining. These parameters include time-dependent stiffness/strength, creep and shrinkage and steel fibre parameters. In addition, the influence of lining thickness and tunnel diameter on the time-dependent behaviour of the shotcrete lining is evaluated. The results indicate the efficiency of the shotcrete lining to resist the disturbances and transfer the loads shortly after application. The results compatible with the results of other literatures, which elucidates the efficiency of the shotcrete model to predict the steel fibre shotcrete behaviour in numerical simulation.